Plan de intervención psicológica desde el enfoque cognitivo-conductual para la depresión - Herrera Herrera, Glenda Elizabeth (My University, 2019)
The objective of the following essay is to adapt a therapeutic plan to improve the emotional state in depression based on the Aaron Beck model. Depression is a disease that presents a combination of different cognitive, behavioral and somatic symptoms. This pathology occurs mostly in women than in men; most often occurs between 18 and 29 years of age. The risk factors associated with this problem are: being a woman, isolation, economic difficulties, exposure to traumas, stressful experiences, personal history of other mental health problems, family history, drug use, interpersonal and marital problems, among others. Beck's cognitive model explains depression as the result of the person's evaluations of their experiences; this model summarizes it in cognitive schemas, which are cognitive structures that organize information; cognitive triad which consists in having a negative vision of oneself, of the future and of the world; and the processing of information, which is about cognitive biases among which generalization, selective abstraction, personalization, maximization, absolutism. We propose an intervention plan with a cognitive behavioral approach based on scientific evidence that helps to increase pleasurable activities, decrease distorted thoughts and develop coping skills in the face of this problem.
El objetivo del siguiente ensayo es adaptar un plan terapéutico para mejorar el estado emocional en la depresión basado en el modelo de Aaron Beck. La depresión es una enfermedad que presenta una combinación de diferentes síntomas cognitivos, conductuales y somáticos. Esta patología se presenta mayormente en mujeres que en hombres; con mayor frecuencia ocurre entre los 18 y los 29 años de edad. Los factores de riesgo asociados a este problema son: ser mujer, aislamiento, dificultades económicas, exposición a traumas, experiencias estresantes, antecedentes personales de otros problemas de salud mental, antecedentes familiares, el uso de drogas, problemas interpersonales y matrimoniales, entre otros. El modelo cognitivo de Beck explica la depresión como el resultado de valoraciones que tiene la persona sobre sus experiencias, este modelo lo resume en esquemas cognitivos, los cuales son estructuras cognitivas que organizan la información; tríada cognitiva la cual consiste en tener una visión negativa de sí mismo, del futuro y del mundo; y el procesamiento de la información, que se trata de sesgos cognitivos entre los que destaca la generalización, abstracción selectiva, personalización, maximización, absolutismo. Se propone un plan de intervención con enfoque cognitivo conductual basado en evidencia científica que ayude a aumentar las actividades placenteras, disminuir pensamientos distorsionados y desarrollar habilidades de afrontamiento ante este problema.
Keywords: MODELO COGNITIVO; DEPRESION; FACTOR DE RIESGO; INTERVENCION